A New Application of Acetate‐Based Ionic Liquids: Potential Usage as Drying Materials. Issue 3 (6th February 2014) - Chen, Yu; Cao, Yuanyuan; Mu, Tiancheng
Abstract Acetate‐based ionic liquids (AcILs) are green and designable solvents applied in many fields. However, AcILs are found to be highly hygroscopic. On the one hand, the high hygroscopicity of AcILs influences their properties and structures. On the other hand, this hygroscopic property renders AcILs, and especially [EMIM][Ac], potentially useful as drying materials, a new application of AcILs proposed in this paper. These two traits could be interconnected, interdependent, and interconvertible, which implies that a shortcoming of AcILs, i.e., their hygroscopicity, leading to changes in their physical properties, could be turned into a useful feature, e.g., the potential usage as drying material, if it is dealt with properly.